2017
DOI: 10.1103/physreve.95.013111
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of flame acceleration in open or vented obstructed pipes

Abstract: While flame propagation through obstacles is often associated with turbulence and/or shocks, Bychkov et al. [Physical Review Letters 101 (2008) Starting with an inviscid approximation, we subsequently incorporate hydraulic resistance (viscous forces) into the analysis for the sake of comparing its role to that of a jet-flow driving acceleration. It is shown that hydraulic resistance is actually not required to drive flame acceleration. In contrast, this is a supplementary effect, which moderates acceleration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 18 publications
2
10
0
Order By: Relevance
“…In addition, a unique trend is noticed for the -impact on . propagation, the oscillations agree with the modelling [35,36], experiments [34], and theory [36] of flames in channels with both ends open or vented in terms that all of the studies [35][36][37] identified steady flame propagation prior to fast acceleration. The regime of the quasi-steady propagation is also influenced by the blockage ratio α and the thermal expansion ratio Θ.…”
Section: Corrugated Flamessupporting
confidence: 81%
See 3 more Smart Citations
“…In addition, a unique trend is noticed for the -impact on . propagation, the oscillations agree with the modelling [35,36], experiments [34], and theory [36] of flames in channels with both ends open or vented in terms that all of the studies [35][36][37] identified steady flame propagation prior to fast acceleration. The regime of the quasi-steady propagation is also influenced by the blockage ratio α and the thermal expansion ratio Θ.…”
Section: Corrugated Flamessupporting
confidence: 81%
“…Bychkov et al [36], developed an analytical formulation for flame propagated in obstructed channels with both ends opened. The theorical formulation for inviscid flows is presented below.…”
Section: Premixed Flames In Channels With Both Ends Openmentioning
confidence: 99%
See 2 more Smart Citations
“…It was suggested that the interaction of the expanded gas with the obstructed walls of the channel obstacle creates a turbulent feedback, which promotes the flame speed rapidly [11]. A similar result has been recently identified in the analytical study of FA in a vented obstructed channel by Bychkov et al [12]. The acceleration characteristics in channels with both ends open were found to be considerably weaker as compared to that in semi-open channels.…”
Section: Combustion Theory Fundamentalssupporting
confidence: 70%